A mathematical modeling arising in the chemical systems and its approximate numerical solution - Kumar S.; Khan Y.; Yildirim A. (My University, 2025)
In this paper, a mathematical modeling of reaction-diffusion Brusselator system with fractional time derivative is proposed. Reaction-diffusion response is obtained with fractional-order elements as well as integer-order elements. Fractional reaction-diffusion Brusselator system is used for modeling of certain chemical reaction-diffusion processes. The implementation of homotopy perturbation method proved extremely effective and highly suitable. Numerical results are presented graphically and reveal that the homotopy perturbation method is an effective and convenient method to solve fractional-order reaction-diffusion Brusselator system. © 2011 Curtin University of Technology and John Wiley & Sons, Ltd.